Primitive hemocholecyst: about 7 observations - Praderi, Raúl; Mate, Miguel; Grezzi, Roberto (Cirugía del Uruguay, 1972)
Pathogeny of hemocholecysts is analyzed; they may be primitive in the gall bladder or secondary to a haemobilia of hepatic or pedicular origin. In the seven cases treated by the authors they found lithiasis of the gallbladder in all cases and in five of thethere was ohstruction of the cystic duct. Furthermore, in four cases there was cancer of the gall bladder. In two cases hemoperitoneum and haemobilia occurred. The latter does not always appear since often the gall bladder is excluded due to obstruction of the cystic duct.